IbM PENINGKATAN PERSONAL HYGIENA PADA SISWA SD NEGERI KEC. KOTA BARU - Tina Yuli Fatmawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Health problems that often occur in elementary school age children are diseases related to personal hygiene / personal hygiene and the environment such as good and correct brushing, hand washing habits with soap, and personal hygiene. Diseases that often arise are diarrhea, helminthiasis, toothache and so on. The problem with partners faced today is that there are still many elementary school students who do not understand the importance of personal hygiene. The purpose of Community Service provides an understanding of the importance of personal hygiene in elementary school students. Community service activities have been carried out in May-June 2017 to fifth grade students of SDN 206 with a total of 86 students. The service method uses survey, lecture, discussion and simulation approaches. The results obtained are all students of class V understand about Personal Hygiena and want to apply in everyday life. It is recommended to the school especially UKS officers and class teachers to always provide motivation, monitor elementary school students in increasing knowledge and implementing personal hygiene so that students can avoid disease